Efficacy of manual acupuncture vs. placebo acupuncture for generalized anxiety disorder (GAD) in perimenopausal women: a randomized, single-blinded controlled trial - Liu, Xin; Li, Meichen; Xie, Xiaoyan; Li, Yingjia; Li, Keyi; Fan, Jingqi; He, Jun; Zhuang, Lixing (Frontiers in Psychiatry, 2023)
Background Generalized anxiety disorder (GAD) is common among perimenopausal women. Acupuncture may be an effective treatment for GAD, but evidence is limited. The pathogenesis of GAD is not yet clear, but it is related to the hypothalamic-pituitary-adrenal axis and its excretion, cortisol (CORT), and the adrenocorticotropic hormone (ACTH). The objective of this study is to evaluate the efficacy of manual acupuncture (MA) vs. placebo acupuncture (PA) for perimenopausal women with GAD. Methods This study is a single-center, randomized, single-blind clinical trial conducted in the First Affiliated Hospital of Guangzhou University of Chinese Medicine. A total of 112 eligible patients with GAD were randomly assigned (1:1) to receive MA (n = 56) or PA (n = 56) three times per week for 4 weeks. The primary outcome measure was the HAMA score. The secondary outcome measures were the GAD-7 and PSQI scores and the levels of CORT and ACTH. The evaluation will be executed at the baseline, 2 weeks, the end of the treatment, and a follow-up 3-month period. Results Significant improvements in HAMA (p < 0.001, η2p = 0.465), GAD-7 (p < 0.001, η2p = 0.359) and ACTH (p = 0.050) values were found between T0 and T2 in the MA group compared to the PA group. No difference in PSQI (p = 0.613, η2p = 0.011) and CORT (p = 0.903) was found between T0 and T2 in the MA group compared to the PA group. Long-term improvements in HAMA (p < 0.001, p < 0.001) were found in the MA group and PA group. Conclusion This study was the first completed study to evaluate the efficacy of acupuncture and placebo acupuncture for GAD in perimenopausal patients. Results suggested that placebo acupuncture has a therapeutic effect, however, acupuncture had a greater therapeutic effect than placebo acupuncture. This study supports the effectiveness of acupuncture and thereby contributes to extended treatment options for GAD. Clinical trial registration:http://www.chictr.org.cn, Chinese Clinical Trial Registry, ID: ChiCTR2100046604. Registered on 22 May 2021.